STRATEGY FORMULATION FOR DEVELOPING BATIK TULIS - Indah Eko Suryani; Lukytawati Anggraeni; Ujang Suryadi (Indonesian Journal of Business and Entrepreneurship (IJBE), 2015)
The objective of this study was to formulate a development strategy in order to maintain the existence of Batik Tulis Rolla Junior. The study used a case study approach with Rumah Batik Tulis Rolla Junior as the research object. The data were analyzed by a value chain approach to determine the internal and external conditions influencing the existence of the Batik Tulis Rolla Junior. Furthermore, this study also used the analysis of Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE) Matrix, SWOT, dan Quantitative Strategic Planning Matrix (QSPM) to create the development strategy. The results show that the strategies that can be recommended to Rolla Junior include 1) increasing the capital by Kredit Usaha Rakyat (KUR) program, 2) conductiong expansions to other regencies, 3) creating a website/blog  to promote and perform business transactions, 4) increasing the frequency in joining exhibitions or EXPO both in regional and national levels, 5) conducting researches to solve the problem of coloring which requires sun rays, 6) conducting cooperations with raw material suppliers (backward integration), and 7) finding alternative suppliers of raw materials especially from the areas closer to Jember district.Keywords: development strategy, batik tulis Rolla Junior, SWOT, QSPMABSTRAKPenelitian ini bertujuan merumuskan strategi pengembangan sehingga dapat menjaga eksistensi Batik Tulis Rolla Junior. Penelitian menggunakan pendekatan studi kasus dengan Rolla Junior sebagai objek penelitiannya. Data dianalisis dengan pendekatan rantai nilai untuk mengetahui kondisi internal dan eksternal yang berpengaruh terhadap Batik Tulis kemudian menggunakan analisis Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External (IE) Matrix, SWOT, dan Quantitative Strategic Planning Matrix (QSPM) untuk menyusun strategi pengembangan Batik Tulis Rolla Junior. Hasil penelitian menunjukkan bahwa strategi-straegi prioritas yang dapat direkomendasikan kepada Rolla Junior yaitu 1) peningkatan permodalan melalui program Kredit Usaha Rakyat (KUR), 2) melakukan ekspansi ke luar daerah Jember, 3) membuat situs web/blog untuk mempromosikan dan transaksi jual beli produk, 4) peningkatan kuantitas keikutesertaan dalam acara pameran atau EXPO baik di tingkat regional maupun nasiona, 5) melakukan penelitian untuk mengatasai kendala pewarnaan yang membutuhkan sinar matahari, 6) melakukan kegiatan kerja sama dengan pemasok bahan baku (integrasi ke belakan, dan 7) mencari alternatif daerah pemasok bahan baku khususnya yang lebih dekat dengan kabupaten Jember.Kata kunci: strategi pengembangan, batik tulis Rolla Junior, SWOT, QSPM